Анализ ударного режима работы линейного электродвигателя для источника сейсмических колебаний - Милых, Владимир Иванович; Ткаченко, Сергей Валериевич (НТУ "ХПИ", 2010)
The mathematical model of linear impulsive electric motor is presented. Motor has the cylindrical coaxial electromagnetic system. The mathematical model includes calculation correlations of electromagnetic and mechanical parameters. It allowed to conduct the numeral calculations of transitional process, that correspond to the shock mode of engines work. The temporal functions of sizes which characterize work of the engine are obtained.
Analysis of the shock mode of operations of linear electric motor for seismic oscillations source
Keywords: электродвигатели; линейный импульсный электродвигатель; ударный рабочий режим; математическая модель